Mobility Analysis of the Lumbar Spine with a Dynamic Spine-Correction Device - Wojciech Kaczmarek; Łukasz Pulik; Paweł Łęgosz; Krzysztof Mucha (Sensors, 2023)
According to data, 60–70% of the world’s population experience low-back pain (LBP) at least once during their lifetime, often at a young or middle age. Those affected are at risk of having worse quality of life, more missed days at work, and higher medical care costs. We present a new rehabilitation method that helps collect and analyze data on an ongoing basis and offers a more personalized therapeutic approach. This method involves assessing lumbar spine rotation (L1–L5) during torso movement using an innovative dynamic spine correction (DSC) device designed for postural neuromuscular reeducation in LBP. Spinal mobility was tested in 54 patients (aged 18 to 40 years) without LBP. Measurements were made with 12-bit rotary position sensors (AS5304) of the DSC device. During exercise, the mean lumbar spine rotation to the right was greater (4.78° ± 2.24°) than that to the left (2.99° ± 1.44°; p < 0.001). Similarly, the maximum rotation to the right was greater (11.35° ± 3.33°) than that to the left (7.42° ± 1.44°; p < 0.0001). The measurements obtained in the study can serve as a reference for future therapeutic use of the device.